The Comparison of Women Image in Russian and English Literature - Kodirova Gulshan (International Journal on Orange Technologies, 2021)
This article is devoted to comparing the description of women in both Russian and English literature. Both literature have always been distinguished by the depth of its ideological content, its relentless striving to pose and solve vital problems, its humane attitude to man, and the reality of its depiction of reality. Russian and English writers tried to reveal the best features of our people in female images. In no other literature in the world do we meet such beautiful and chaste women who are distinguished by their faithful and loving hearts, their unique spiritual beauty.